Alkyl ferulic acid esters: Evaluating their structure and antibacterial properties - Song, Wei; Xin, Jiaying; Yu, Chong; Xia, Chungu; Pan, Yu (Frontiers in Microbiology, 2023)
In order to improve the lipophilicity and biological activity of ferulic acid(FA), four alkyl ferulic acid esters (FCs) with different alkyl chain lengths were obtained by fatty alcohols (including 1-propanol(C3), 1-hexanol(C6), nonanol(C9) and lauryl alcohol(C12)) modification in this study. The effect of FCs molecules with different alkane chains on antibacterial activities against foodborne pathogens (Escherichia coli (EC), Pseudomonas aeruginosa (PA), Staphylococcus aureus(SA) and Bacillus subtilis(BS)) and their mode of action were investigated. Results showed that the antibacterial activity of FCs increased after esterification, but the antibacterial activity increased first and then decreased with the extension of the alkyl chain of the FCs. Hexyl ferulate (FC6) showed the best antibacterial activities against Escherichia coli and Pseudomonas aeruginosa (MIC for Escherichia coli was 0.5mg/mL, MIC for Pseudomonas aeruginosa was 0.4mg/mL). And Propyl ferulate(FC3) and FC6 showed the best antibacterial activities Staphylococcus aureus and Bacillus subtilis (MIC for Staphylococcus aureus was 0.4mg/mL, The MIC of Bacillus subtilis was 1.1mg/mL). In addition, the growth, alkaline phosphatase (AKP) activity, bacterial biofilm, bacterial cell morphology, membrane potential and cell contents leakage of PA after different FCs were investigated, which found that FCs could damage the cell wall of PA and showed different effects on the PA cell biofilm. FC6 showed the best inhibition on the biofilm formation of PA cells, which caused the surface of PA cells to be rough and wrinkled. Some PA cells showed aggregation and adhesion, even rupture. The membrane hyperpolarization was obvious, which appeared as holes, leading to cell contents leakage (protein and nucleic acid). All these results concluded that the antibacterial activities FCs against foodborne pathogens depended on different fatty alcohol esterification of FA. FC6 showed the best inhibition on PA due to its effect on PA cell walls and biofilms and the leak of the cell contents.